Outcomes in acute myeloid leukemia among older adults: a five-year retrospective cohort from a Brazilian public hospital - Mota Segundo, Hercules Amorim; Duarte, Fernando Barroso (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Acute myeloid leukemia (AML) remains a significant public health issue in the Brazilian public healthcare system. A retrospective chart review was conducted for patients diagnosed with AML between 2019 and 2024 at a university hospital in northeastern Brazil. Six patients underwent intensive chemotherapy with daunorubicin and cytarabine. Fourteen patients received low-intensity therapy (venetoclax combined with low-dose cytarabine, venetoclax and azacitidine, and azacitidine monotherapy). The overall one-year survival rate in this age group was 28.9%, with a median overall survival of 8.3 months. When stratified by treatment intensity, patients receiving low-intensity therapy had a median overall survival of 10.9 months, compared to 1.1 month for those receiving intensive chemotherapy and 1.5 month for those receiving supportive care alone. The incorporation of low intensity therapies may reduce toxicity and improve survival among elderly patients in low- and middle-income countries.